Effect of Biopotting Quality on Growth and Morphological Quality of Jackfruit Artocarpus Heterophyllus Lamk. Seedlings - Munif Said Hassan; Abdul Hayat Kasim; Rizki A.P. Santosa; Santosa, Slamet (Universitas Pendidikan Ganesha, 2023)
The use of polybags causes an increase in plastic waste and can damage roots when seedlings are planted. Biopotting as a seedling media affects the growth and morphological quality of jackfruit seedlings. Biopotting is made from clay, compost from fruits waste of rambutan, jackfruit, durian, and compost from market and tapioca flour. The results of the chemical analysis of biopotting samples contained organic C ranged 42-44%, total N ranged 0.21-0.35%, total P ranged 28.14-38.25mgkg-1, K ranged 0.90-1.13me/100g and pH ranged 4.08-6.68. Analysis of the physical quality containing water ranged 2.04-3.09%, density ranged 0.42-0.50gcm-3, water absorption ranged 200-242% and the level of damage to biopotting ≤ 2%, included in the undamaged category. The growth and morphological quality of jackfruit seedlings aged 60 days had a height ranged 17.85-27.6cm, an average stem diameter ranged 0.43-0.47cm, a leaf number ranged 3-4 strands, a root length ranged 12.5-16.8cm and a morphological quality index ranged 0.092-0099. This study concluded that M4 biopotting had the best chemical and physical qualities resulting in the highest growth and morphology of the jackfruit Artocarpus heterophyllus Lamk seedlings.